Evaluasi Sistem Informasi Kesehatan dengan Pendekatan Health Metrics Network di Dinas Kesehatan Kota Pagar Alam - Widyaningsih; Lilis Suryani; Heriziana (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Data and information are strategic resources in health development and management. A health information system is considered effective if it can give information support in a decision making process through all levels. Health information system evaluation aims to ensure the efficiency of a health information system and its ability to provide quality information. The study aimed to determine description of health information system evaluation results in Pagar Alam Public Health Office. The study was carried on by using Health Metric Network (HMN) as tools. The study is a descriptive evaluative design with mixed method approach. The study subjects were 9 Health Information System workers in Pagar Alam Public Health Office. Study data was collected by doing interview and observation. Data analysis was done by using Health Metric Network (HMN) version 4.00. The result of health information system evaluation using six components within HMN instrument was within the range of 41-60% which means that the system exists but inadequate. The conclusion of this study is that health information system in Pagar Alam Public Health Office has been carried on well enough, but requires improvements in its data management